Sasak Community Traditions as a Tool for Halal Tourism Promotion in Improving Tourist Visits to Lombok - ., Jumaidin; ., Hariono; Johari, Muhamad; Sumardani, Rizki (Akademi Komunitas MAPINDO, 2023)
The purpose of this study is to find out how the process of begawe below and nyongkolan customs in the SasakLombok tribe community and to find out how the role of begawe below and nyongkolan customs as apromotional event for halal tourism on the island of Lombok, the research location is carried out in the touristvillages of Sade, Setanggur, and Darek, in this study using qualitative methods and using primary and secondarydata types, the data collection methods of this study are interviews, documentation, observation and literaturestudy, for research data analysis using data validity tests, namely credibility, transferability, dependability, andconfirmability. Credibility criteria basically replace the concept of validity of qualitative. the results in this studyshow that. begawe beleq and nyongkolan customs in the sasak lombok tribe there are several processes thatmust be followed by the sasak lombok tribe community including pembarak, pesila'an, pisolo, dulang momot,serakalan, praje ponggok, sorong serah and nyongkolan, The begawe beleq event and nyongkolan customs inthe sasak lombok community will greatly affect the progress of tourism on the island of Lombok as evidencedby the various roles played by the government and the community towards the progress of tourism on theisland of LombokKeywords: Tradition, Promotion, Halal Tourism and Tourist of Visitors